Pengenalan Karakter Walisongo dengan Metode Mind Mapping pada Anak Remaja - Dimas Prasetyo; Ikhwanuddin Ikhwanuddin; Muhammad Yusron Maulana El-Yunusi; Sebastianus Priambodo; Didit Darmawan; Mohammad Djaelani; Bambang Triono (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
The era of globalization brings changes by causing religion, which was originally a public issue, to turn into a privacy issue. The development of religion which has become a private matter makes teenagers as identity seekers tend to implement it. The purpose of this activity is to preserve Walisongo so that it is not eliminated from the historical facts of the spread of Islam. The method applied in this service is Participatory Action Research (PAR). The results of this service activity have a positive impact on teenagers because know more about the nine saints of God who spread Islam in the archipelago and increase their understanding of the character of the saints and their struggles. The impact of getting to know the teenagers in Bebekan Tengah Village, Taman District, Sidoarjo Regency increased their admiration for the walisongo struggle which resulted in an increase in pilgrimages to the walisongo graves.